Impact of Obesity on Shock of Dengue Hemorrhagic Fever Among Children at Tertiary Care Hospital of Bangladesh - Ferdous, Jannatul; Hassan, Quamrul; Sultana, Sabina; Zabeen, Fahmida (Bangladesh Journal of Infectious Diseases, 2025)
Background: The association between nutritional status and dengue infection is still considered controversial. Objective: The purpose of the present study was to find out the relationship (association) between obesity and shock of dengue hemorrhagic fever (DHF) in pediatric patient. Methodology: This case-control study was conducted on children up to 14 years of age with dengue hemorrhagic fever admitted from May 2021 to November 2021 at the Pediatric Department of Evercare Hospital, Dhaka, Bangladesh. Data were analyzed after collection of demographic and clinical data of 71 enrolled children, out of which 40 DHF with shock and 31 DHF without shock. Overweight & obesity was assessed with BMI according to CDC growth chart. Statistical analysis of the results was obtained by using windows computer software with Statistical Packages for Social Sciences (SPSS-version 22). Results: Out of 71 patients, prevalence of DHF with shock is 56.3% and DHF without shock is 43.6%. Obesity was found 20(50%) in DHF with shock and 5(16.1%) in DHF without shock which showed statistically significant. Furthermore, pleural effusion (p=0.001), ascites (p=0.022), pulmonary oedema (p=.006), highest HCT > 46% (0.013%) also had significant association with shock event. Conclusion: There is significant relationship between obesity, pleural effusion, ascites, pulmonary oedema and highest hematocrit level with DHF with shock. Weak pulse was more common sign of shock followed by narrow pulse pressure, hypotension, cold clammy skin and decrease urine output. Bangladesh Journal of Infectious Diseases, December 2024;11(2):115-120